Caracterização física e química de frutos de barueiros (Dipteryx alata VOG.) de ocorrência natural no cerrado do Estado de Goiás, Brasil - Vera, Rosângela (2007)
Barueiro (Dipteryx alata Vog.) is a species native to the Brazilian Cerrado with high fruit yield and high nutritional value. The objective of this work was to study the physical and chemical characteristics of barueiro fruits (baru) harvested from plants in eleven locations in the state of Goiás, in the Cerrado biome. In each location twelve trees in full production were randomly selected. Approximately sixty fruits were collected from each tree, and from those fruits a sample of ten fruits was taken to study some physical characteristics. Another sample of twenty fruits was taken for chemical analyses. For the physical characterization, the following variables were evaluated: mass, length, width and thickness of the whole fruit; epicarp+mesocarp mass (pulp); almond and endocarp mass, and almond length, width and thickness. For the chemical determinations a composite sample was obtained from ground almonds extracted from the endocarp. Moisture content, whole protein, ethereal extract, phosphorus, potash, calcium, magnesium, sulfur, copper, iron, manganese and zinc were determined in three replicates as well as the fatty acid composition. The data obtained was submitted to the analysis of variance and means comparison by Tukey test at 5% level of probability. The descriptive statistical analysis was applied to data obtained from the physical analyses of the mass of the fruits and almonds. The average fruit mass varied from 26.08 to 37.20 g, and the average almonds mass varied from 1.11 to 1.48 g. The fruits had a 51.15% average of pulp, 44.69% of endocarp, and the almonds had 4.16%. The mass of the almond was positively correlated to fruit mass, fruit length, fruit width and fruit thickness. The average moisture content of the almond varied from 2.93 to 5.07g (100 g)-1. The protein content varied from 25.16 to 27.69 g (100)-1 and the ethereal extract from 32.42 to 37.36 g (100)-1. The average content of saturated fatty acids varied from 19.930 to 25.74%, and the unsaturated fatty acids varied from 73.47 to 79.19%. The most common fatty acids were oleic, whose average content varied from 45.58 to 48.98g (100 g)-1 and linoleic, whose average content varied from 22.83 to 29.71 g (100 g)-1. The mineral macronutrients that showed the highest concentrations were potash, phosphorus and sulfur. Calcium and magnesium were present in the lowest concentrations. The mineral micronutrients that showed the lowest concentrations were copper, manganese and zinc. Iron was present in the highest concentration